A phase 2 multicenter study of ublituximab, a novel glycoengineered anti-CD20 monoclonal antibody, in patients with relapsing forms of multiple sclerosis. (March 2021) - Fox, Edward; Lovett-Racke, Amy E; Gormley, Matthew; Liu, Yue; Petracca, Maria; Cocozza, Sirio; Shubin, Richard; Wray, Sibyl; Weiss, Michael S; Bosco, Jenna A; Power, Sean A; Mok, Koby; et al.
Background: Ublituximab, a novel monoclonal antibody (mAb) targeting a unique epitope on the CD20 antigen, is glycoengineered for enhanced B-cell targeting through antibody-dependent cellular cytotoxicity (ADCC). Greater ADCC may allow lower doses and shorter infusion times versus other anti-CD20 mAbs. Objective: The objective was to determine optimal dose, infusion time, and activity of ublituximab in relapsing multiple sclerosis. Methods: This is a phase 2, placebo-controlled study. Patients received three ublituximab infusions (150 mg over 1–4 hours on day 1 and 450–600 mg over 1–3 hours on day 15 and week 24) in six dosing cohorts. The primary endpoint was B-cell depletion. Results: In all cohorts ( N  = 48), median B-cell depletion was >99% by week 4, maintained at weeks 24 and 48. Most common adverse events (AEs) were infusion-related reactions (all grade 1–2), with no apparent increased incidence at shorter infusion times. There were no AE-related discontinuations. At weeks 24 and 48, no T1 gadolinium-enhancing lesions ( p  = 0.003) and a 10.6% decrease in T2 lesion volume ( p  = 0.002) were detected. The annualized relapse rate was 0.07; 93% remained relapse free on study. Overall, 74% of patients had no evidence of disease activity (NEDA). Conclusion: Ublituximab was safely infused as rapid as 1 hour, producing robust B-cell depletion and profound reductions in magnetic resonance imaging (MRI) activity and relapses.